Methane production potential of pulp mill sludges: microbial community and substrate constraints. Issue 21 (5th January 2022) - Chan-Yam, Kelly; Meyer, Torsten; Scott, J Ashley; Basiliko, Nathan
ABSTRACT: Sludges from pulp and paper mills represent a major ecological and environmental cost, and anaerobic digestion represents a method of waste reduction and energy recovery for these mills. This study compared methane production potential and microbial communities across 11 primary- and biosludges from five pulp and paper mills using various mill processes. We measured methane production from sludges in anaerobic batch reactor experiments over 64 days. Sludges were incubated with and without added substrate to test for organic substrate limitation versus inhibition of methanogens. Initial microbial communities and changes to community composition were determined using Illumina MiSeq for metabarcoding of bacterial and archaeal 16S rRNA genes. Mean methane production potential varied greatly between sludges (0.002–79 mL CH4 g –1 TS). Among primary sludges, kraft mill sludge produced more methane than other mill types. For these other mills, biosludge produced more methane than primary sludge, which had evidence of methanogen inhibition. Microbial communities and diversity were influenced by the initial community composition, and high methane production was only seen in sludges with high diversity. A number of sludges innately produced substantial methane and may be targets for further modelling and larger scale testing of anaerobic digestion. Abstract : Anaerobic digestion of 11 pulp and paper mill sludges reveals a wide range in methane production correlated with microbial diversity.